Viscoplastic Analysis of Fiber Reinforced Polymer Matrix Composites Under Various Loading Conditions - R. M. Guedes (2009)
The present study aims modeling the viscoplastic behavior of polymer matrix composite laminates under different loading conditions. The adopted model is based on the one-parameter plasticity model employed to predict the plastic part of the recognized nonlinear behavior of fiber composites [C.T. Sun and J.L. Chen, J. Compos. Mater, 23,1009 (1989)]. This model evolved to a three-parameter constitutive viscoplastic model used to describe successfully the strain-rate dependent mechanical behavior. Based on this model, designated as 3PV, a numerical implementation was made, based on the Classical Laminate Theory (CTL), to simulate non-linear behavior of general laminates. The validation of this numerical implementation was performed using experimental data reported in literature. The first step was to assess the model predictions under high strain rates. The model was able to model high strain rate mechanical response, of an epoxy system reinforced with glass fibers, between 10 and 2,500 s(-1). Furthermore the model proved to be reasonable accurate to simulate creep, stress relaxation and constant strain rate loading of the same material system under high temperatures. Following the experimental observations of vsicoplasticity strain evaluation during load and unloading made by Kim and Tsai [J. Compos. Mater. 36(6), 745 (2002)], a simple model modification is suggested. This modified model proved accurate enough to simulate relaxation successfully of a composite during loading and unloading. POLYM. COMPOS., 30:1601-1610, 2009. (c) 2008 Society of Plastics Engineers